(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
Issues of rational resource use are considered and a method of gravitational enrichment and processing of industrial waste from the Kadamzhai Antimony Plant (KSK) is described. Gravity enrichment was carried out on a concentration table, which is the process of separating solid particles by density and size in the pulp layer. The work revealed that the separation of metallic antimony from technogenic waste depends on the fraction of the substances, therefore, for enrichment they used up to a fraction of 0.5 to 0.7 mm. It has been established that the concentration table, in the process of gravity of technogenic waste, enriches metallic antimony up to 65%. It has been shown that for good separation of slag and matte, the specific gravity of the slag must be lower than the specific gravity of the matte by at least one. In one work shift (8 hours), 400 kg of antimony concentrate is obtained from 5 tons of technogenic waste